An evaluation of structure planning under the Land Use Planning Ordinance, 1985 (No. 15 of 1985) - Olivier, Andre P.(Andries Philippus) (Stellenbosch : Stellenbosch University, 2012)
Study project (M. Town and regional planning) -- University of Stellenbosch, 1990.